Measurement and analysis of atmospheric optical turbulence in a near-maritime environment. (30th September 2020) - Jellen, Christopher; Nelson, Charles; Brownell, Cody; Burkhardt, John; Oakley, Miles
Abstract: The index of refraction structure constant, C n 2, characterizing the intensity of optical turbulence, describes the disruption of a propagating electromagnetic beam passing through an inhomogeneously heated turbulent environment. In order to improve predictive models, it is critical to develop a deeper understanding of the relationships between environmental parameters and optical turbulence. To that end, an overwater, 890 m scintillometer link was established along the Chesapeake Bay adjacent to the Severn River in Annapolis, Maryland. Specifically, C n 2 data from the scintillometer, as well, as numerous meteorological parameters were collected over the period of approximately 15 months to characterize a scintillometer link in the near-maritime environment. The characteristics of this near-maritime link were distinct from those observed in prior over-land and open ocean links. Further, existing macro-meteorological models for predicting C n 2 from environmental parameters developed for open-ocean links were shown to perform poorly in the near-maritime environment. While the offshore adapted macro-meteorological model demonstrated lower prediction error, this study suggests that new models could be developed to reduce C n 2 prediction error in the near-maritime environment. The complete data set, including C n 2 measurements, and to our knowledge, one of the first to extend beyond one year, is available.